Emotional pictures in the brain and their interaction with the task: A fine-grained fMRI coordinate-based meta-analysis study - Serafino Paolo Mansueto; Zaira Romeo; Alessandro Angrilli; Chiara Spironelli (NeuroImage)
The impacting research on emotions of the last decades was carried out with different methods. The most popular was based on the use of a validated sample of slides, the International Affective Pictures System (IAPS), divided mainly into pleasant, neutral and unpleasant categories, and on fMRI as a measure of brain activation induced by these stimuli. With the present coordinate-based meta-analysis (CBMA) based on ALE approach, we aimed to unmask the main brain networks involved in the contrast of pleasant vs. neutral and unpleasant vs. neutral IAPS slide categories. Furthermore, we included studies employing both IAPS and non-IAPS (but analogously validated) pictures, a condition termed as IAPS EXTENDED. After selecting 97 papers published in the 2000–2023 interval, the planned contrasts were analyzed by also considering their interaction with the Load factor of the concomitant task, which comprised the conditions: No Load (passive viewing), Low-Load tasks and High-Load tasks. We analyzed a total of 152 experiments (106 focusing on the negative vs. neutral contrast; 46 reporting positive vs. neutral contrasts). We additionally performed conjunction and contrast analyses. Results confirmed outcomes of past meta-analyses on the involvement of a number of cortical and subcortical paralimbic and limbic regions during unpleasant picture processing, but the increase of the pubblications on this topic in last years, together with a more fine-grained analysis, allowed us to find also the involvement of additional areas, such as the right middle frontal gyrus, left inferior frontal gyrus (BA 9), posterior cingulate, and left inferior parietal lobule. Concerning passive viewing and low-load tasks, a clear frontal asymmetry emerged with greater right prefrontal activation (BA9) to unpleasant vs. pleasant pictures, whereas, during No Load tasks only, left frontal dominance to pleasant vs. unpleasant stimuli was found (BA13). The unpleasant vs. neutral comparison on High-Load tasks (the pleasant condition had an insufficient sample size) revealed a specific lateralization of several areas of the right hemisphere (STG-BA 38, MFG-BA 46, FG-BA 37), whereas, in the other load conditions, the inferior frontal gyrus was right lateralized, but the main activated regions were bilateral or left lateralized. Results are discussed considering the effects of both valence and task/load variables, and the involvement of hippocampus/amygdala, hemispheric asymmetries of emotions, the occipito-temporal areas, several sub-regions of the prefrontal/orbitofrontal cortex, and an extended motor network.